2021
DOI: 10.3390/ijms22115444
|View full text |Cite
|
Sign up to set email alerts
|

C60 Fullerene Reduces 3-Nitropropionic Acid-Induced Oxidative Stress Disorders and Mitochondrial Dysfunction in Rats by Modulation of p53, Bcl-2 and Nrf2 Targeted Proteins

Abstract: C60 fullerene as a potent free radical scavenger and antioxidant could be a beneficial means for neurodegenerative disease prevention or cure. The aim of the study was to define the effects of C60 administration on mitochondrial dysfunction and oxidative stress disorders in a 3-nitropropionic acid (3-NPA)-induced rat model of Huntington’s disease. Animals received 3-NPA (30 mg/kg i.p.) once a day for 3 consecutive days. C60 was applied at a dose of 0.5 mg/kg of body weight, i.p. daily over 5 days before (C60 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 75 publications
1
11
0
Order By: Relevance
“…Against this background, the use of C 60 fullerenes can enhance and promote further activation of the above processes. This is proved by our preliminary studies, which confirmed the fact that the use of C 60 fullerene under extreme conditions affects the rapid formation of adaptive reactions of the body by affecting such transcription factors as Nrf2 (NF-E2-related factor 2), NF-κB, and p53 [44]. The glutathione system plays an important role in the implementation of antiradical and antiperoxide cell protection [22].…”
Section: Biochemical Analysissupporting
confidence: 68%
“…Against this background, the use of C 60 fullerenes can enhance and promote further activation of the above processes. This is proved by our preliminary studies, which confirmed the fact that the use of C 60 fullerene under extreme conditions affects the rapid formation of adaptive reactions of the body by affecting such transcription factors as Nrf2 (NF-E2-related factor 2), NF-κB, and p53 [44]. The glutathione system plays an important role in the implementation of antiradical and antiperoxide cell protection [22].…”
Section: Biochemical Analysissupporting
confidence: 68%
“…Fullerene C60 (an allotrope of carbon) neutralizes ROS and possesses a SOD-like activity [ 137 ], making it a suitable compound for preventing oxidative stress [ 138 , 139 ]. In 3-NP treated male rat Wistar model of HD, pre- and post-treatment with C60 prevented mitochondrial dysfunction and enhanced nuclear Nrf2 protein expression in the brain [ 140 ].…”
Section: Nrf2 and Hdmentioning
confidence: 99%
“…It was also established that administration of CBL prevented the decline in Bcl-2 protein concentration in rat striatum induced by rotenone [10]. It is known that expression of antiapoptotic protein Bcl-2 is modulated by oxidative stress: enhanced OS and altered level of antioxidants occurred in the brains of Bcl-2 -deficient mice [29] as well as at acute 3-nitropropionic acid intoxication [3]. So, one of the mechanisms through which CBL counteracts elevated OS in PD could be regulation of Bcl-2 protein expression in neuronal cells.…”
Section: Resultsmentioning
confidence: 95%
“…Increased ROS generation and impaired antioxidant defense could both contribute to OS development in neurodegenerative disorders [2,3]. Oxidative damage may contribute to the aggregation of protein into brain structures such as Lewy bodies which form the key histological hallmark of the second most prevalent neurodegenerative disease worldwide -Parkinson's disease (PD) [2].…”
Section: Introductionmentioning
confidence: 99%